a(a(d(d(x1)))) → d(d(b(b(x1))))
a(a(x1)) → b(b(b(b(b(b(x1))))))
b(b(d(d(b(b(x1)))))) → a(a(c(c(x1))))
c(c(x1)) → d(d(x1))
↳ QTRS
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QTRS Reverse
a(a(d(d(x1)))) → d(d(b(b(x1))))
a(a(x1)) → b(b(b(b(b(b(x1))))))
b(b(d(d(b(b(x1)))))) → a(a(c(c(x1))))
c(c(x1)) → d(d(x1))
a(a(d(d(x1)))) → d(d(b(b(x1))))
a(a(x1)) → b(b(b(b(b(b(x1))))))
b(b(d(d(b(b(x1)))))) → a(a(c(c(x1))))
c(c(x1)) → d(d(x1))
d(d(a(a(x)))) → b(b(d(d(x))))
a(a(x)) → b(b(b(b(b(b(x))))))
b(b(d(d(b(b(x)))))) → c(c(a(a(x))))
c(c(x)) → d(d(x))
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ DependencyPairsProof
↳ QTRS Reverse
d(d(a(a(x)))) → b(b(d(d(x))))
a(a(x)) → b(b(b(b(b(b(x))))))
b(b(d(d(b(b(x)))))) → c(c(a(a(x))))
c(c(x)) → d(d(x))
B(b(d(d(b(b(x1)))))) → C(x1)
B(b(d(d(b(b(x1)))))) → A(c(c(x1)))
A(a(x1)) → B(b(x1))
A(a(d(d(x1)))) → B(x1)
A(a(d(d(x1)))) → B(b(x1))
A(a(x1)) → B(b(b(b(b(x1)))))
B(b(d(d(b(b(x1)))))) → A(a(c(c(x1))))
A(a(x1)) → B(b(b(x1)))
B(b(d(d(b(b(x1)))))) → C(c(x1))
A(a(x1)) → B(b(b(b(x1))))
A(a(x1)) → B(b(b(b(b(b(x1))))))
A(a(x1)) → B(x1)
a(a(d(d(x1)))) → d(d(b(b(x1))))
a(a(x1)) → b(b(b(b(b(b(x1))))))
b(b(d(d(b(b(x1)))))) → a(a(c(c(x1))))
c(c(x1)) → d(d(x1))
↳ QTRS
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QTRS Reverse
B(b(d(d(b(b(x1)))))) → C(x1)
B(b(d(d(b(b(x1)))))) → A(c(c(x1)))
A(a(x1)) → B(b(x1))
A(a(d(d(x1)))) → B(x1)
A(a(d(d(x1)))) → B(b(x1))
A(a(x1)) → B(b(b(b(b(x1)))))
B(b(d(d(b(b(x1)))))) → A(a(c(c(x1))))
A(a(x1)) → B(b(b(x1)))
B(b(d(d(b(b(x1)))))) → C(c(x1))
A(a(x1)) → B(b(b(b(x1))))
A(a(x1)) → B(b(b(b(b(b(x1))))))
A(a(x1)) → B(x1)
a(a(d(d(x1)))) → d(d(b(b(x1))))
a(a(x1)) → b(b(b(b(b(b(x1))))))
b(b(d(d(b(b(x1)))))) → a(a(c(c(x1))))
c(c(x1)) → d(d(x1))
↳ QTRS
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ RuleRemovalProof
↳ QTRS Reverse
B(b(d(d(b(b(x1)))))) → A(c(c(x1)))
A(a(x1)) → B(b(x1))
A(a(d(d(x1)))) → B(x1)
A(a(d(d(x1)))) → B(b(x1))
A(a(x1)) → B(b(b(b(b(x1)))))
A(a(x1)) → B(b(b(x1)))
B(b(d(d(b(b(x1)))))) → A(a(c(c(x1))))
A(a(x1)) → B(b(b(b(x1))))
A(a(x1)) → B(b(b(b(b(b(x1))))))
A(a(x1)) → B(x1)
a(a(d(d(x1)))) → d(d(b(b(x1))))
a(a(x1)) → b(b(b(b(b(b(x1))))))
b(b(d(d(b(b(x1)))))) → a(a(c(c(x1))))
c(c(x1)) → d(d(x1))
A(a(d(d(x1)))) → B(x1)
A(a(d(d(x1)))) → B(b(x1))
POL(A(x1)) = x1
POL(B(x1)) = x1
POL(a(x1)) = x1
POL(b(x1)) = x1
POL(c(x1)) = 1 + 2·x1
POL(d(x1)) = 1 + 2·x1
↳ QTRS
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ Narrowing
↳ QTRS Reverse
B(b(d(d(b(b(x1)))))) → A(c(c(x1)))
A(a(x1)) → B(b(x1))
A(a(x1)) → B(b(b(b(b(x1)))))
B(b(d(d(b(b(x1)))))) → A(a(c(c(x1))))
A(a(x1)) → B(b(b(x1)))
A(a(x1)) → B(b(b(b(x1))))
A(a(x1)) → B(b(b(b(b(b(x1))))))
A(a(x1)) → B(x1)
a(a(d(d(x1)))) → d(d(b(b(x1))))
a(a(x1)) → b(b(b(b(b(b(x1))))))
b(b(d(d(b(b(x1)))))) → a(a(c(c(x1))))
c(c(x1)) → d(d(x1))
B(b(d(d(b(b(x0)))))) → A(d(d(x0)))
B(b(d(d(b(b(c(x0))))))) → A(c(d(d(x0))))
↳ QTRS
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QTRS Reverse
A(a(x1)) → B(b(x1))
A(a(x1)) → B(b(b(b(b(x1)))))
A(a(x1)) → B(b(b(x1)))
B(b(d(d(b(b(x1)))))) → A(a(c(c(x1))))
B(b(d(d(b(b(x0)))))) → A(d(d(x0)))
A(a(x1)) → B(b(b(b(x1))))
B(b(d(d(b(b(c(x0))))))) → A(c(d(d(x0))))
A(a(x1)) → B(b(b(b(b(b(x1))))))
A(a(x1)) → B(x1)
a(a(d(d(x1)))) → d(d(b(b(x1))))
a(a(x1)) → b(b(b(b(b(b(x1))))))
b(b(d(d(b(b(x1)))))) → a(a(c(c(x1))))
c(c(x1)) → d(d(x1))
↳ QTRS
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ QDPOrderProof
↳ QTRS Reverse
A(a(x1)) → B(b(x1))
A(a(x1)) → B(b(b(b(b(x1)))))
A(a(x1)) → B(b(b(x1)))
B(b(d(d(b(b(x1)))))) → A(a(c(c(x1))))
A(a(x1)) → B(b(b(b(x1))))
A(a(x1)) → B(b(b(b(b(b(x1))))))
A(a(x1)) → B(x1)
a(a(d(d(x1)))) → d(d(b(b(x1))))
a(a(x1)) → b(b(b(b(b(b(x1))))))
b(b(d(d(b(b(x1)))))) → a(a(c(c(x1))))
c(c(x1)) → d(d(x1))
The following pairs can be oriented strictly and are deleted.
The remaining pairs can at least be oriented weakly.
A(a(x1)) → B(x1)
Used ordering: Polynomial interpretation [25]:
A(a(x1)) → B(b(x1))
A(a(x1)) → B(b(b(b(b(x1)))))
A(a(x1)) → B(b(b(x1)))
B(b(d(d(b(b(x1)))))) → A(a(c(c(x1))))
A(a(x1)) → B(b(b(b(x1))))
A(a(x1)) → B(b(b(b(b(b(x1))))))
POL(A(x1)) = 8 + 6·x1
POL(B(x1)) = 4·x1
POL(a(x1)) = 4 + x1
POL(b(x1)) = 8
POL(c(x1)) = 0
POL(d(x1)) = 0
a(a(x1)) → b(b(b(b(b(b(x1))))))
b(b(d(d(b(b(x1)))))) → a(a(c(c(x1))))
a(a(d(d(x1)))) → d(d(b(b(x1))))
c(c(x1)) → d(d(x1))
↳ QTRS
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ QDPOrderProof
↳ QTRS Reverse
A(a(x1)) → B(b(x1))
A(a(x1)) → B(b(b(b(b(x1)))))
B(b(d(d(b(b(x1)))))) → A(a(c(c(x1))))
A(a(x1)) → B(b(b(x1)))
A(a(x1)) → B(b(b(b(x1))))
A(a(x1)) → B(b(b(b(b(b(x1))))))
a(a(d(d(x1)))) → d(d(b(b(x1))))
a(a(x1)) → b(b(b(b(b(b(x1))))))
b(b(d(d(b(b(x1)))))) → a(a(c(c(x1))))
c(c(x1)) → d(d(x1))
The following pairs can be oriented strictly and are deleted.
The remaining pairs can at least be oriented weakly.
A(a(x1)) → B(b(x1))
A(a(x1)) → B(b(b(b(b(x1)))))
B(b(d(d(b(b(x1)))))) → A(a(c(c(x1))))
A(a(x1)) → B(b(b(x1)))
A(a(x1)) → B(b(b(b(x1))))
Used ordering: Polynomial interpretation [25]:
A(a(x1)) → B(b(b(b(b(b(x1))))))
POL(A(x1)) = 14 + 2·x1
POL(B(x1)) = 12 + 2·x1
POL(a(x1)) = 9 + x1
POL(b(x1)) = 2 + x1
POL(c(x1)) = 2·x1
POL(d(x1)) = 2·x1
a(a(x1)) → b(b(b(b(b(b(x1))))))
b(b(d(d(b(b(x1)))))) → a(a(c(c(x1))))
a(a(d(d(x1)))) → d(d(b(b(x1))))
c(c(x1)) → d(d(x1))
↳ QTRS
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ DependencyGraphProof
↳ QTRS Reverse
A(a(x1)) → B(b(b(b(b(b(x1))))))
a(a(d(d(x1)))) → d(d(b(b(x1))))
a(a(x1)) → b(b(b(b(b(b(x1))))))
b(b(d(d(b(b(x1)))))) → a(a(c(c(x1))))
c(c(x1)) → d(d(x1))
a(a(d(d(x1)))) → d(d(b(b(x1))))
a(a(x1)) → b(b(b(b(b(b(x1))))))
b(b(d(d(b(b(x1)))))) → a(a(c(c(x1))))
c(c(x1)) → d(d(x1))
d(d(a(a(x)))) → b(b(d(d(x))))
a(a(x)) → b(b(b(b(b(b(x))))))
b(b(d(d(b(b(x)))))) → c(c(a(a(x))))
c(c(x)) → d(d(x))
↳ QTRS
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QTRS Reverse
↳ QTRS
d(d(a(a(x)))) → b(b(d(d(x))))
a(a(x)) → b(b(b(b(b(b(x))))))
b(b(d(d(b(b(x)))))) → c(c(a(a(x))))
c(c(x)) → d(d(x))